Lactobacillus gasseri LG08 and Leuconostoc mesenteroides LM58 exert preventive effect on the development of hyperuricemia by repairing antioxidant system and intestinal flora balance - Liang, Lizhen; Meng, Zihui; Zhang, Fei; Jianguo, Zhu; Fang, Shuguang; Hu, Qingang; Tang, Xuna; Li, Yanan (Frontiers in Microbiology, 2023)
Currently, hyperuricemia has shown a surprisingly rising trend, which attracts widespread attention due to potentially major health risks. Considering the inevitable side effects of long-term medicine, probiotics are emerging as potential therapeutics due to their ability to improve uric acid metabolism and superior safety. In our study, two strains of probiotics, Lactobacillus.gasseri LG08 (LG08) and Leuconostoc.mesenteroides LM58 (LM58) isolated from kimchi were evaluated for the prebiotic properties in vitro and uric-lowering effects in vivo. Here, we further investigated whether these probiotics exert different effects in prevention and treatment. In vivo indicators and intestinal flora immunity revealed that both LG08 and LM58 significantly prevent the development and progression of hyperuricemia, repair the antioxidant system and maintain intestinal flora balance in healthy rats, especially LM58. After hyperuricemia was formed, although the effect of LG08 and LM58 could decrease the level of uric acid, the effect to reverse and repair antioxidant levels in the body was limited. These findings have important implications for hyperuricemia prevention and therapy, and provided more mechanistic insights into the effect of probiotics in hyperuricemia.